Youth Perceptions of and Experiences With Opioids for Pain Management: Intersecting Stigmas and Ambivalence. (June 2022) - Nairn, Stephanie A.; Audet, Marion; Anzarouth, Lauren; Stewart, Sherry H.; Isaacs, Jason Y.; Conrod, Patricia
ABSTRACT: Objective: There is very little in-depth qualitative research regarding youth experiences with medical use of prescription opioids and this is concerning as some youth are shown to be at risk for future nonmedical opioid use, addiction, and overdose as a result of medical use of opioids in adolescence. We sought to understand and characterize youth experiences with prescription opioids, such that researchers and healthcare professionals can improve both opioid and pain-related treatment and intervention programs for young people. Methods: We recruited participants through postering and television advertisements from the Emergency, Orthopedics, Dental, and Oncology/Hematology departments at a local children's hospital. We performed 3 focus groups, 5 in-depth interviews and one youth summit (n = 11 youth) for a total of 25 youth who had experience with prescription opioids. The results were analyzed using a thematic analysis approach. Results: The participants were heterogeneous and were youth who had been prescribed opioids due to surgery for scoliosis, cancer, brain surgery, dialysis, and other acute injuries. Youth simultaneously emphasized the positive (eg, to improve physiological functioning and to cope with mental (emotional) struggles related to their conditions in some instances) and negative effects of opioids (eg, adverse side effects and concerns about whether opioid use was related to other psychological struggles). The experience of ambivalence coincided with youth experience of intersecting stigma(s) related to their physiological conditions and their use of opioids. Youth discussed several solutions for how to improve youth-provider interactions in the context of these experiences and perceptions. Conclusion: Youth encounter a dearth of nuanced information about opioids during illness experiences and recovery and the experience of opioid-related ambivalence may be compounded by the everyday struggles associated with their conditions including intersecting prejudicial attitudes and stigmatization. Consistent with an interdisciplinary approach to prescription opioid use and pain rehabilitation, service providers could consider engaging in nuanced, empathetic, and empowering discussions with youth and provide alternatives or adjuncts to opioids for pain management. Abstract : Objectif: Il existe très peu d'études qualitatives approfondies sur l'expérience des jeunes en lien avec l'usage d'opioïdes d'ordonnance à des fins médicales, ce qui est préoccupant, puisque certains de ces jeunes se révèlent à risque d'usage d'opioïdes à des fins non médicales, de dépendance et de surdose conséquemment à l'usage d'opioïdes à des fins médicales à l'adolescence. Nous avons cherché à comprendre et à caractériser les expériences des jeunes en lien avec les opioïdes d'ordonnance afin que les chercheurs et les professionnels de la santé puissent améliorer à la fois les programmes d'intervention liés aux opioïdes et au traitement de la douleur chez les jeunes. Méthodologie: Nous avons recruté des participants au moyen d'affiches et d'annonces télévisées à l'urgence et dans les départements d'orthopédie, de dentisterie et d'hémato-oncologie d'un hôpital pour enfants local. Nous avons animé trois groupes de discussion, cinq entrevues approfondies et un sommet (n = 11 jeunes) auprès de 25 jeunes ayant une expérience d'usage d'opioïdes d'ordonnance. Les résultats ont été soumis à une analyse thématique. Résultats: Les participants formaient un groupe hétérogène de jeunes ayant reçu une prescription d'opioïdes à la suite d'une intervention chirurgicale au cerveau ou pour une scoliose, un cancer, lors d'une dialyse ou pour une autre atteinte grave. Les jeunes ont souligné autant les effets positifs (p. ex., l'amélioration du fonctionnement physiologique et la gestion des émotions négatives parfois liées à leur problème de santé) que négatifs (p. ex., les effets indésirables et les inquiétudes à savoir si l'usage d'opioïdes était lié à d'autres difficultés psychologiques) des opioïdes. Les expériences d'ambivalence coïncidaient avec la stigmatisation liée à leur problème physiologique et leur usage d'opioïdes. Les jeunes ont proposé des solutions pour améliorer leurs interactions avec les fournisseurs dans le contexte de ces expériences et perceptions. Conclusion: Les jeunes manquent de renseignements nuancés sur l'usage d'opioïdes pendant la maladie et la récupération, et l'ambivalence liée aux opioïdes peut être exacerbée par les difficultés quotidiennes associées à leur problème de santé, y compris les préjugés et la stigmatisation qui les accompagnent. Dans la logique d'une approche interdisciplinaire sur l'usage d'opioïdes d'ordonnance et de rééducation sensitive, les fournisseurs de soins pourraient envisager de s'entretenir avec les jeunes de façon nuancée, empathique et habilitante et leur offrir d'autres options ou des traitements d'appoint pour la douleur.